Adoption of snowball sampling technique with distance boundaries to assess the productivity issue faced by micro and small cocoa producers in Cusco - Jalca, Angie (2020)
The food supply chain has gained impulse over the past few years induced by the rising global demand for food; therefore, much emphasis is placed upon examining this class of supply chains. It also faces constant production, storage, and distribution challenges, wherein the key link for proper operation is the farmer, who engages in the agricultural sector, heavily impacted by low crop productivity, which interfer with economic development at a national level. Consequently, it is important to assess those farmers who belong to micro and small enterprises in the agricultural sector. Due to the characteristics of the population, a nonprobability sampling technique was used to assess micro and small cocoa producers in La Convención Province, Cusco, Peru. To such end, a snowball sampling model with distance boundaries was adopted because the population is unknown and hard to reach.